2011
DOI: 10.1007/s13213-011-0216-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cold adaptation on the survival of Listeria monocytogenes in ice-cream formulations during long-term frozen storage

Abstract: This is the first study to evaluate the survival potential of cold-adapted Listeria monocytogenes in icecream. Cold adaptation enhances survival of this pathogen in ice-cream during the first period of storage compared to non-adapted cells. The viable population of cold-adapted and non-adapted cells was 3 log (36 days) and 4.3 log (27 days), respectively, lower than the initial population (6.3 log) in inoculated ice-cream. This behavior raises concerns for food safety. The viable population of both cold-and no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…It is not known whether increasing the temperature to −10 or 0°C would affect the survival of L. monocytogenes in artificially contaminated or process-contaminated samples. Published studies have examined the population dynamics of L. monocytogenes in ice cream at different frozen temperatures (Palumbo and Williams, 1991;Dean and Zottola, 1996;Gougouli et al, 2008;Mastronicolis et al, 2011). For example, it was determined in one study that L. monocytogenes populations in artificially contaminated ice cream did not significantly differ between storage temperatures of −5, −15, −23, or −33°C (Gougouli et al, 2008).…”
Section: Short Communicationmentioning
confidence: 99%
See 1 more Smart Citation
“…It is not known whether increasing the temperature to −10 or 0°C would affect the survival of L. monocytogenes in artificially contaminated or process-contaminated samples. Published studies have examined the population dynamics of L. monocytogenes in ice cream at different frozen temperatures (Palumbo and Williams, 1991;Dean and Zottola, 1996;Gougouli et al, 2008;Mastronicolis et al, 2011). For example, it was determined in one study that L. monocytogenes populations in artificially contaminated ice cream did not significantly differ between storage temperatures of −5, −15, −23, or −33°C (Gougouli et al, 2008).…”
Section: Short Communicationmentioning
confidence: 99%
“…For example, it was determined in one study that L. monocytogenes populations in artificially contaminated ice cream did not significantly differ between storage temperatures of −5, −15, −23, or −33°C (Gougouli et al, 2008). However, when assessing cold-adapted versus unadapted L. monocytogenes, another study concluded that cold adaptation increased the pathogen's ability to survive during the first month of storage at −20°C (Mastronicolis et al, 2011). Because in-process contaminants had been exposed to freezing temperatures in the ice cream for many weeks before the current study was conducted, they may be regarded as cold adapted; however, no differences in survival between pathogen contamination states (in-process/cold-adapted vs. artificial) were observed.…”
Section: Short Communicationmentioning
confidence: 99%
“…Listeria monocytogenes has been associated with a variety of food products, including dairy foods, meat, poultry, and seafood as well as fruits and vegetables (Farber and Peterkin, 2000; Mastronicolis et al, 2011). In 2008, 1,381 confirmed human cases of listeriosis were reported in the European Union and the reported case-fatality rate was 20.5% [European Food Safety Authority (EFSA), 2010].…”
Section: Introductionmentioning
confidence: 99%